Single-Phase Frequency Response of the Induction Motor for the determination of its electrical parameters - Becerra Areválo, Gilberto (2002)
This research work has for fundamental object to show a new method of identification of the induction three-phase motor equivalent circuit parameters.This new method consist of to use the result of the single phase test as a base test to variable frequency.The single-phase is performed using a variables voltage and frequency from a power supply (Ward-Leonard Group).Key words: Induction Motor, Single phase test, Equivalent Circuit, Parameters.